2013
DOI: 10.1007/s00264-013-2032-0
|View full text |Cite
|
Sign up to set email alerts
|

The anterior subcutaneous internal fixator (ASIF) for unstable pelvic ring fractures. Clinical and radiological mid-term results

Abstract: Purpose The purpose of this study was to determine the outcome of unstable type C pelvic fractures treated with posterior stabilisation and the anterior subcutaneous internal fixator (ASIF). Methods Altogether, 36 consecutive patients were treated for unstable type C pelvic ring fractures using posterior stabilisation and ASIF. After a minimum of 18 months, the clinical and radiological outcome was retrospectively investigated. Results Overall, three patients (8.3 %) died, and 31 patients (86 %) were available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
0
39
1
1
Order By: Relevance
“…We ensured that the screw head remained above deep fascia to prevent compression of femoral nerve and inguinal ligament. We used 7mm-diameter polyaxial pedicle screws in comparison to that used by Vaidya 17,30,31,33 In contrast to previous studies, there were no cases of heterotopic ossification in our series at a mean follow-up of 34.9+/À4.1 months (Table 4). The incidence of this complication varies from 0 to 42% in previous studies.17 ,28,31,33 It is unclear why there were no cases of heterotopic ossification in our series.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We ensured that the screw head remained above deep fascia to prevent compression of femoral nerve and inguinal ligament. We used 7mm-diameter polyaxial pedicle screws in comparison to that used by Vaidya 17,30,31,33 In contrast to previous studies, there were no cases of heterotopic ossification in our series at a mean follow-up of 34.9+/À4.1 months (Table 4). The incidence of this complication varies from 0 to 42% in previous studies.17 ,28,31,33 It is unclear why there were no cases of heterotopic ossification in our series.…”
Section: Discussionmentioning
confidence: 85%
“…[14][15][16] To overcome the complications of anterior external fixation, to improve patient comfort and facilitate early mobilization, several innovative techniques of minimally invasive anterior pelvic ring stabilization have been described in recent years. 17,[26][27][28][29][30][31][32][33][34] The "INFIX" is one such technique which utilizes the already established principles of external fixation. Biomechanical studies have shown that the INFIX has superior stability with respect to axial stiffness and stiffness at pubic symphysis, in the management of vertically and rotationally unstable pelvic ring injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
“…nachgewiesen werden[26], er bleibt jedoch der Symphysenplatte unterlegen. In einer klinischen Nachuntersuchung an 36 Patienten haben Müller et al[10] 65 % gute und sehr gute Ergeb-…”
unclassified